Lactic acid bacteria in cooked hams – Sources of contamination and chances of survival in the product. (March 2016) - Dušková, Marta; Kameník, Josef; Lačanin, Ines; Šedo, Ondrej; Zdráhal, Zbyněk
Abstract: The aim of this study is microbiological analysis of individual technological operations during the industrial production of cooked hams, focusing on lactic acid bacteria (LAB). Samples were during the course of the entire cooked ham production cycle in May–June (Experiment I) and November–December (Experiment II). A total of 215 samples were taken and subsequently tested. The difference in the occurrence of LAB in meat before thermal processing resulted from the initial level of contamination of the raw material. A reduction to the number of LAB from 4.0 to 5.0 log CFU/g of meat to a value of practically zero occurred during the thermal processing. The LAB population increased during storage of the finished products. A level of 7.0 log CFU/g was reached in slices of ham in the modified atmosphere after three (Experiment I) or two (Experiment II) weeks of storage, respectively. LAB of the genera Leuconostoc ( Leuc. carnosum, Leuc. mesenteroides and Leuc. gelidum ) occurred most frequently in samples of cooked ham after thermal processing. These species were also isolated from the production environment. Lactobacillus sakei, Lbc. curvatus and Weissella viridescens were other species of LAB that were isolated from samples after thermal processing. Highlights: The input raw material was evidently a source of LAB. In meat before cooking LAB were detected at an amount up to 4.0–6.0 log CFU/cm 2 . A reduction of the number of LAB to a value of zero occured during heat treatment. The LAB population increased during subsequent storage of cooked hams at 2 ± 2 °C. LAB of the genera Leuconostoc occurred most frequently in samples of cooked hams.